Medial humeral epicondylar lesions in the canine elbow - de Bakker, E.; Samoy, Y.; Gielen, I.; Ryssen, Van B. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
A calcified fragment near the medial epicondyle of the humerus was originally described as an ununited medial epicondyle in 1966. Since then several papers reported similar lesions as a cause of elbow lameness. The aetiology and clinical significance of those lesions is poorly known. This paper gives an overview of the veterinary and human literature in an attempt to explain the aetiology and to suggest a diagnostic protocol and treatment plan.
Keywords: Review; enthesopathy; tendinopathy; medial humeral epicondyle; dog